(untitled) (Journal of Economic Additions, 2025)
This Study aims to analyze the impact of using internal auditing as a tool for risk management at the National Well Drilling (ENTP) in hassi messoud ouargla,in the applied part, The researchers relied, in the applied part, on content analysis of official internal audit documents and reports of the company, while employing the descriptive method to examine the theoretical framework. The study’s findings revealed a positive relationship between the quality of the company’s internal audit performance and the effectiveness of risk management. Internal auditing contributed to improving risk response and reducing its impact through control recommendations Keywords:Internal Auditing, Internal Control, Risks, Risk Management, ENTP Company Jel Classification Codes: M42.G32.D81